Police-civil relations for good governance - Fernando, Laksiri; Social Scientists Association of Sri Lanka (Colombo : Social Scientists' Association, 2005)
Research study conducted in Kalutara District, Sri Lanka.
Keywords: Police-community relations -- Sri Lanka -- Kalutara District